Ubiquitin and protein degradation. - Deshaies, Raymond Joseph, 1961- (Methods in enzymology, 2005)
Ubiquitin and Protein Degradation, Part B will cover chemical biology, ubiquitin derivatives and ubiquitin-like proteins, deubiquitinating enzymes, proteomics as well as techniques to monitor protein degradation. The chapters are highly methodological and focus on application of techniques. *Second part of the Ubiquitin and Protein Degration series *Topics include: E1 Enzymes, E2 Enzymes, E3 Enzymes, Proteasomes, and Isopeptidases.